Physicochemical Properties of Modified Palado Seed Flour (Aglaia sp.) from Pregelatinization, Cross-Linking and Acetylation - Rahman, Syamsul; Salengke, S.; Tawali, Abu Bakar; Mahendradatta, Meta (Pakistan Journal of Nutrition, 2018)
Background and Objective: The palado seed flour increase the economic value and shelf life of processed palado products. The aim of this study was to know the physicochemical characteristics of modified palado seed flour. Materials and Methods: This study was conducted in three stages: The first stage was flour production from palado seed, the second stage was flour modification using pregelatinization, cross-linking and acetylation and third the stage was analysis of physical and chemical properties. These analyses included proximate content analysis, such as evaluation of the carbohydrate, energy, starch, amylose and amylopectin contents. Meanwhile, the physical properties evaluated include the yield, degree of whiteness, density, heat viscosity and cold viscosity. Results: The results of the analysis of the physicochemical properties of modified palado seed flour showed a water content (6.72-8.23%), an ash content (1.25-3.26%), a fat content (9.46-9.75%), a protein content (5.46-8.75%), a carbohydrate content (71,04-73.50%), an energy content (402-417 kcal), a starch content (57.99-63.98%), an amylose content (0.44-0.85) and an amylopectin (57.44-63.13%). The resulting yield was in the range of 60.35-68.91%, the degree of whiteness was 45.23-61.69%, of the density was 0.59-0.69 g mL–1, the heat viscosity was 6.20-524.00 cP and cold viscosity was 6.45-313.00 cP. Conclusion: It is concluded that palado seed flour is useful as an alternative flour based on its physicochemical properties, before and after modification.